2009
DOI: 10.1590/s1517-83822009000100024
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional changes in powdered red pepper upon in vitro infection of Aspergillus flavus

Abstract: Quantitative losses in various biochemical constituents like capsaicin, carotenes, ascorbic acid, polyphenols, mineral matter, sugars (soluble and insoluble), protein and fat were estimated after the successful growth of Aspergillus flavus for 30 days on powdered red pepper. The fungal biomass was measured by ergosterol content and Aflatoxin B1 by HPLC. Amongst the various nutritional constituents evaluated for nutritional losses and changes the highest nutritional loss was reported in total carotenoids (88.55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…This suggests that pepper and ginger with high flavonoids contents will exhibit these properties. The high carotenoid content of pepper compared to virtually none in garlic and ginger is not surprising as carotenoids are largely responsible for the red colour of peppers (Tripathi and Mishra, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that pepper and ginger with high flavonoids contents will exhibit these properties. The high carotenoid content of pepper compared to virtually none in garlic and ginger is not surprising as carotenoids are largely responsible for the red colour of peppers (Tripathi and Mishra, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Total solid content of the pulp samples ranged from 32.6-41.2%, and the total soluble solids content varied from 31.0 to 39.5°Bx. The chemical analysis (Tripathi and Mishra 2009a) of bael pulp was carried out, and results are presented in Table 1. Pulp was extracted by addition of distilled water (1:1 w/w) to facilitate seed removal (Roy and Singh 1979) followed by subsequent straining through 20 mesh stainless steel sieve.…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, it has been revealed that C. annuum is a highly nutritive fruit that contains several macronutrients such as protein, carbohydrate, fats, and dietary fiber (Ismail, Anjum, Mamon, & Kazi, 2011;Tripathi & Mishra, 2009). The composition of macronutrients present in C. annuum is summarized in Table 4, and the nutrient present in the pungent type is summarized in Table 5.…”
Section: Macronutrients In Capsicum Annuummentioning
confidence: 99%